The Effect of Servant Leadership, Job Satisfaction, and Physical Work Environment on Job Performance - Hamid, Hilmi; Kurniawan, Ignatius Soni; Yulianto, Eko (Jurnal Ilmu Manajemen Profitability, 2025)
The quality of healthcare services is highly dependent on the performance of nurses, which in turn is influenced by leadership style, job satisfaction, and the physical work environment. Although previous studies have examined these factors, limited research has focused on the combined effects of servant leadership, job satisfaction, and work environment within Indonesian hospital settings. This study aims to analyze the influence of these variables on job performance, with a particular emphasis on permanent nurses at RSU PKU Muhammadiyah Bantul. A quantitative approach was employed by distributing structured questionnaires to 64 respondents selected through accidental sampling from a total population of 176 nurses. The collected data were analyzed using multiple linear regression to test the relationships among the variables. The results reveal that servant leadership and the physical work environment exert positive but statistically insignificant effects on job performance. In contrast, job satisfaction demonstrates a significant and dominant effect, highlighting its essential role in enhancing the overall performance of nurses. These findings indicate that improvements in job satisfaction can generate stronger outcomes in terms of productivity, commitment, and service quality compared to leadership style and work environment factors. Theoretically, this study contributes to the literature on organizational behavior in healthcare by clarifying the relative importance of satisfaction in performance improvement. Practically, it provides actionable insights for hospital administrators to prioritize strategies that foster job satisfaction as a key driver of sustainable workforce performance.